Descriptive Study of Physiotherapy Services Used in the South Kalimantan Region in 2020 - Maulida Wijaya Putri (ITKES Wiyata Husada Samarinda, 2021)
Health services, including physiotherapy services, are carried out in almost all health care facilities such as clinics, health centers, and hospitals. Physiotherapy services are one form of health services needed by the community. In order to provide physiotherapy services, physiotherapists can provide various types of modalities or physiotherapy services in the form of electro therapy, actino therapy, hydro therapy, manual therapy or exercise therapy. Almost all health care facilities in South Kalimantan have physiotherapy services, but there is no data on the number and types of physiotherapy services used by health care facilities in the South Kalimantan region. This study aims to determine the types of physiotherapy services that are widely used by health care facilities in South Kalimantan. This study uses a descriptive approach. Based on the results of the study, it was found that 35 respondents (67.3%) used electrotherapy very often and 30 respondents (57.7%) used actino therapy very often. These two types of physiotherapy services are the most widely used by health care facilities in the South Kalimantan region in 2020